2020
DOI: 10.24252/eternal.v61.2020.a3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Students’ Motivation on Learning Writing Skills Through Inquiry Approach

Abstract: This present study investigated students’ motivation for learning writing skills through an inquiry approach. The research methodology that was used the type of descriptive research using correlational, where the researchers wanted to know the motivation of students as well as see differences in student motivation in learning writing skills through an inquiry approach.  This study used purposive sampling and the respondents were the tenth-grade students of MAN 3 Makassar consist of two classes. They are the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…According to research in Indonesia, the critical thinking abilities of junior high school students (Ariza Rahmadana Hidayati et al, 2021;Dewi et al, 2018) and high school students (Elfrida et al, 2017;Sudrajat et al, 2021) are inadequate. Students' writing abilities still need attention to be improved in learning using the inquiry model (Ali & Ulker, 2020;Cetin & Eymur, 2017;Erenler & Cetin, 2019;Hamsina, 2020;Palupi et al, 2020), which can facilitate students to be more independent in building their understanding and being meaningful and can contribute to improving critical thinking abilities (Lin et al, 2021;Maknun, 2020). Building a classroom learning environment that focuses on learning through inquiry is an important factor for effective classroom management (Garza & Arreguín-Anderson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to research in Indonesia, the critical thinking abilities of junior high school students (Ariza Rahmadana Hidayati et al, 2021;Dewi et al, 2018) and high school students (Elfrida et al, 2017;Sudrajat et al, 2021) are inadequate. Students' writing abilities still need attention to be improved in learning using the inquiry model (Ali & Ulker, 2020;Cetin & Eymur, 2017;Erenler & Cetin, 2019;Hamsina, 2020;Palupi et al, 2020), which can facilitate students to be more independent in building their understanding and being meaningful and can contribute to improving critical thinking abilities (Lin et al, 2021;Maknun, 2020). Building a classroom learning environment that focuses on learning through inquiry is an important factor for effective classroom management (Garza & Arreguín-Anderson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the inquiry model is a learning model that can improve the writing skills [4] [12][14] [23] [34]. It is also effective in improving student's writing skills in learning Indonesian [38][43] [9].…”
Section: Introductionmentioning
confidence: 99%